EFFECTS OF AMMONIUM SULFATE AND SEAWEED EXTRACT (ALGA21ST) AS FOLIAR SPRAY TO NUTRITION CONTENT OF TWO CULTIVARS OF SWEET CHERRY (PRUNUS AVIUM L.) TRANSPLANTS - & Al-Zubaydi, Yaseen (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was conducted during the two growing seasons 2016 and 2017 in the lath house at the College of Agriculture, Duhok University, Kurdistan Region of Iraq. Uniform and healthy transplants of (2) years old sweet cherry (Prunus avium L.) cultivars (evey loly and shampion) were used. The effects of three levels of Ammonium sulfate (NH4)2SO4) (as source of nitrogen) (0, 3 and 6 gm L-1), three levels of seaweed extracts (alga21st) concentrations (0, 1 and 2 gm.L-1) and their interactions on leaf nutrients status, the content of protein, carbohydrate were investigated. The results showed that cv. evey loly transplants significantly dominated over cv. shampion in leaf N concentration %  and protein % (in second season), leaf S concentration % (in first season) , leaf K concentration % and carbohydrates % (in both season), Ammonium sulfate at concentration 6 gm.L- 1 N significantly increased all traits in both seasons.  Also treated sweet cherry transplant to different level of seaweed extract (alga21st) and especially at 2 gm.L-1 significantly increased most characterized studied in both seasons. The interactions between cultivar and ammonium sulfate significantly enhanced all detected traits particularly interaction between (cv. evey loly and 6 gm.L-1   N) in 2016 and 2017 seasons. Interaction between cultivar and alga21st significantly increased most characteristics in both study seasons. cv.evey loly with 2 gm.L-1 gave positive significant of leaf N concentration % and leaf phosphorous concentration (in 2017 season), leaf K concentration, leaf S concentration %, protein % and carbohydrates % (in both seasons). While combination between cv.shampion and 2 gm.L-1  significantly effect on the leaf P concentration % in first season (2016). Combination between ammonium sulfate and alga21st had the highest significant, The dual interaction between 6 gm.L-1 N +2 gm.L-1 alga21st significantly increased leaf  N concentration %, leaf P concentration %and protein % (in second season), leaf K concentration  and carbohydrate % (in both seasons), leaf S concentration % (in first season). On the other hand interaction between 6 gm.L-1 N +1 gm.L-1 had the highest significant in leaf N concentration %, leaf P concentration % and protein % (in first season). The interaction between cultivar +ammonium sulfate a+ alga21st significantly enhanced all studied traits in both study season.in first season the triple interaction between cv.evey loly +6 gm.L-1 N +1 gm.L-1alga21st significantly increased on leaf N concentration % and protein %, while combination between cv.evey loly +6 gm.L-1   N +2 gm.L-1  alga21st had highest significant in leaf N concentration %, leaf P% and protein % (second season), leaf K concentration and carbohydrate % (in both seasons).